Jamu Kunir Asem: Ethnomedicine Overview by Javanese Herbal Medicine Formers in Yogyakarta - Febri Yuda Kurniawan; Muhamad Jalil; Aziz Purwantoro; Budi Setiadi Daryono; Purnomo (Jurnal Jamu Indonesia, 2021)
Kunir asem is one of the traditional drinks that still survive in Javanese society. The young generation needs to be introduced to the heritage of traditional herbal medicine, so that its existence is maintained. Some people judge that herbal medicine is an ancient traditional drink and does not keep up with the times. The objectives of this study are: (1) Explain the study of etnobotany which make up turmeric acid; (2) Explain how the principle of the benefits of kunir asem is based on the understanding of the seller of herbs in the Province of Yogyakarta. This study uses a qualitative method. The research data was taken with documentation, interviews, and documentation. The research data were analyzed by qualitative descriptive. The conclusion of this study is that biopharmaca plants in kunir asem are turmeric and tamarind, and some are added spices in the form of brown sugar, lemongrass, cardamom, cloves, kedawung, lime, and cinnamon. Herb sellers reveal that kunir asem can promote haids, facilitate digestion, reduce stomach acid, as an antibiotic, fresh body, and eliminate acne.